Khuluma: Using Participatory, Peer-Led and Digital Methods to Deliver Psychosocial Support to Young People Living With HIV in South Africa - Atujuna, Millicent; Simpson, Nikita; Ngobeni, Malebo; Monese, Tebogo; Giovenco, Danielle; Pike, Carey; Figerova, Zuzana; Visser, Maretha; Biriotti, Maurice; Kydd, Anna; Bekker, Linda-Gail (Frontiers in Reproductive Health, 2021)
Khuluma is a psychosocial peer-to-peer mHealth intervention that uses text messaging to facilitate social support groups for adolescents living with HIV (ALWH) with the aim of contributing towards positive health outcomes. Although use of mobile technology in the form of mHealth interventions has proliferated recently in the field of health, published literature describing methods and processes of its application is limited. We present a set of methods and processes utilised to develop and pilot the Khuluma mHealth intervention amongst young people (15-20 years) in South Africa. We recruited and enrolled 52 adolescents (15-20-year olds) from four clinics in Pretoria and Cape Town to participate in a 6-month pilot of Khuluma. Participants were ALWH, aware of their status, on antiretroviral therapy for more than 12 months, and not suffering from severe depression. We conducted four pre and post intervention focus group discussions (FGDs) with a proportion of ALWH (n=36) enrolled in the pilot study using participatory methods. Several processes were utilised to then implement this mHealth psychosocial peer-to-peer intervention among ALWH in a 6-month pilot study. These included engaging ALWH for minor study implementation modifications; forming virtual groups; activating the mHealth platform; facilitating and delivering of the Khuluma intervention. The acceptability of the intervention was informed by follow-up focus group discussions and text message data. The initial participatory processes helped tailor the intervention design to participants’ needs as the peer-led facilitation of the groups allowed for the provision of sensitive psychosocial support that allowed young people to express themselves freely, develop a sense of self-worth, and interact more. The nature of the mobile technology also allowed participants to build friendships beyond their geographic area and interact with their peers in real time. Within the evolving context of Covid-19, establishing evidence-based processes and methods for intervention design and curation in virtual spaces is critical.